Analysis of the Implementation of Limited Face to Face Meeting as an Effort to Prevent Learning Loss Due to the Covid Pandemic Elementary School - Nabilla cahya Suprianto; Fajar Setiawan; Ishmatun Naila (Edumaspul: Jurnal Pendidikan, 2022)
The discovery of the Coronavirus Disease virus or what is often called Covid-19 in Indonesia has caused several impacts, especially in the world of education. With the increase in positive cases of this virus, schools are doing home learning. The implementation of home learning is carried out for a long period of time so that it can result in learning loss. Learning Loss is the non-optimal learning process that results in the loss of specific and general knowledge and skills, a decline in academic achievement and most often an extended gap or discontinuity in education. In this study using descriptive qualitative methods using research techniques of observation, interviews and documentation. The purpose of this study is to describe the implementation of face-to-face meetings limited to elementary school students. The results of this study indicate that limited face-to-face meetings have a positive impact, and limited face-to-face meetings are expected to reduce learning loss.